Improving the use of audio-visual materials and equipment in the teaching of social sciences in the teacher training colleges in Thailand - Tanprayoon, Adul 1947-
The teaching of social studies in the teacher training colleges in Thailand is looked upon in this study with the purpose of suggesting desirable modifications and possible improvements regarding the use of audiovisual materials and equipment in teaching.